2020
DOI: 10.1155/2020/8898430
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics Profile, Prevalence of Extended-Spectrum Beta-Lactamase (ESBL), and Multidrug-Resistant Enterobacteriaceae from Different Clinical Samples in Khartoum State, Sudan

Abstract: One of the global requirements for controlling the occurrence of resistance to antimicrobial drugs is to understanding the resistivity profile of various clinical isolates. Therefore, this study aimed to deliver the indication of different resistant profiles of clinically isolated Enterobacteriaceae from different sources of samples from Khartoum state, Sudan, and to determine the prevalence rate of extended-spectrum beta-lactamase (ESBL), multidrug-resistant (MDR), extensively drug-resistant (XDR), and pandru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…In the present study, K. pneumoniae, E. coli, and P. mirabilis were the major Enterobacterales isolated during the study period. These findings are in accordance with earlier studies from Saudi hospitals and countries in the MENA region [ 20 , 26 , 27 ]. These microorganisms have achieved remarkable antimicrobial resistance and have been increasingly recovered from various clinical samples [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, K. pneumoniae, E. coli, and P. mirabilis were the major Enterobacterales isolated during the study period. These findings are in accordance with earlier studies from Saudi hospitals and countries in the MENA region [ 20 , 26 , 27 ]. These microorganisms have achieved remarkable antimicrobial resistance and have been increasingly recovered from various clinical samples [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, another study from the neighboring country of Sudan reported E. coli and K. pneumoniae as the most commonly isolated Enterobacterales . E. coli was reported as a frequent MDR isolate, whereas ESBL activity was more frequent in K. pneumoniae [ 27 ]. These reports are in accordance with our results on the most common bacterial isolation and ESBL activity, with a slight variation in MDR prevalence among the two bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…These should be considered when evaluating ASP outcomes. It is also important that hospitals monitor resistant rates, especially those of MDR, to target efforts to curb it [ 33 ]. Interesting perspectives are emerging, calling for a radical rethinking of what antimicrobial stewardship programs should entail, such as Vickers et al calling for innovative commercial models to stimulate novel antimicrobial development, and integrating rapid diagnostics and infection control practices within the program [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to data from Asia, Latin America, Europe, and Africa, the dramatic increase in third-generation cephalosporin resistance in Enterobacteriaceae is mainly due to the spread of bla-CTXM-15 ESBL (3)(4)(5),with bla CTXM-15 being the most common ESBL gene worldwide (6,7). While most studies of MDR ESBL-producing Enterobacteriaceae have focused on Escherichia coli (8)(9)(10)(11)(12)(13)(14)(15), few studies have characterized the whole genome of MDR ESBL-producing Klebsiella pneumoniae, even though this agent is one of the most widespread MDR ESBL-producing Enterobacteriaceae associated with extra-intestinal infections both in hospital and community settings (16)(17)(18)(19)(20)(21). Moreover, several strains of K. pneumoniae have been linked to multinational epidemics all over the world (21,22).…”
Section: Introductionmentioning
confidence: 99%